Between Habits of the Heart and Copulation of Clichés: Some Popular American Stories, Mores and Shibboleths - Semrau, Janusz (Studia Anglica Posnaniensia, 2013)
From the very beginning, all manner of ideas, concepts and conceits have been advanced to explain America and Americans - as much to themselves as to others. The paper presents a historical- literary compilation of popular notions of ‘Americanness’ in the guise of random de Tocquevillian observations in general circulation. This is to provoke the question about the degree to which this kind of pervasive discourse may reflect the so-called habits of the heart, as against how at a certain point it may lapse into a Nabokovian copulation of clichés.